Explicit instruction improves the comprehension of Spanish object relatives by young monolingual children - Llompart, Miquel; Dabrowska, Ewa (Language and Cognition, 2024)
The present study assessed the comprehension of Spanish object relative (OR) clauses by 6- and 7-year-old children before and after a brief training session targeting the structural differences between ORs and subject relatives. In addition, we investigated the potential relationships between OR comprehension on the one hand and vocabulary size and non-verbal intelligence quotient (IQ) on the other. Comprehension of ORs was very poor at the pre-test but improved considerably after training. Further improvement was observed between the immediate post-test and a delayed post-test, suggesting that the knowledge acquired during training had been integrated into the children's developing linguistic systems. Non-verbal IQ and vocabulary were not found to predict comprehension accuracy. We take these results to suggest that children's difficulties with ORs are better explained by their experience with this construction than by maturational factors and that explicit contrast and feedback can bolster grammatical development in L1 acquisition.
CRIS-Team Scopus Importer:2024-01-26
Keywords: explicit instruction; first language acquisition; grammatical training; non-verbal intelligence; relative clauses; vocabulary